Kānchūailư̄a phūprasop phai læ kānfư̄nfū phư̄nthī prasop ʻuthokkaphai, wātaphai, læ din thalom, Čhangwat Krabī, 2554 (Samnakngān Čhangwat Krabī, 2011)
On public assistance provision against flood, storm, and mud slide disasters in Krabi Province, Southern Thailand.